-16(5n-14)+2=-80n-323

Simple and best practice solution for -16(5n-14)+2=-80n-323 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16(5n-14)+2=-80n-323 equation:


Simplifying
-16(5n + -14) + 2 = -80n + -323

Reorder the terms:
-16(-14 + 5n) + 2 = -80n + -323
(-14 * -16 + 5n * -16) + 2 = -80n + -323
(224 + -80n) + 2 = -80n + -323

Reorder the terms:
224 + 2 + -80n = -80n + -323

Combine like terms: 224 + 2 = 226
226 + -80n = -80n + -323

Reorder the terms:
226 + -80n = -323 + -80n

Add '80n' to each side of the equation.
226 + -80n + 80n = -323 + -80n + 80n

Combine like terms: -80n + 80n = 0
226 + 0 = -323 + -80n + 80n
226 = -323 + -80n + 80n

Combine like terms: -80n + 80n = 0
226 = -323 + 0
226 = -323

Solving
226 = -323

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5x-7-9-9x+3x= | | -2(4x-2)=3 | | f(x)=3x^3-47x^2+208x-252 | | 5x^7-7x^5+18x^4=0 | | 5(y+2)=-2(9y-1)+7y | | 3cos(2t)=0 | | 8=-z+6 | | 3x^2-4x-11=Y | | 50=20+6n | | .6x+2=x-4 | | 37.2=n-12 | | 9=16-6 | | -3(-7w+5)-2w=3(w-4)-1 | | g^2-h^2+gh= | | 2a^2-20a+18=0 | | -2(3x+7)+3(2x)=65 | | ln(6x-5)+ln(x-1)=ln+5 | | 33-3x=84 | | 4x+7z=8+7y | | 2v-5+2(2v+4)=-4(v+3) | | 30=(230-20)*2Q | | 4n+2.1=9.3 | | x^2+25x^2=13 | | 3.8n+11.1=0.11 | | -82=14x+86 | | a+4.2=6.9 | | -3.6=7.13v | | -44=28+9x | | (3t^2)-6t-24=0 | | 888=-668k | | 2sin^2x+3sinx=0 | | 4x^2=17x-4 |

Equations solver categories